Effect of fabric surface’s cleanliness on its moisture/air permeability - Han Chunyu (Thermal Science, 2021)
A fabric’s moisture/air permeability is a main factor for the fabric design for advanced applications, and no theoretical model was available in literature for an optimal permeability. In this paper, we use the capillary-like effect to elucidate the permeability property, and the effect of nano/micro particles on the fabric’s surface on the permeability is studied by the geometric potential theory. Our theoretical analysis shows that an unclean surface gives a negative impact on the permeability. A superhydrophobic surface is needed to design a good and lasting moisture/air permeability.